Automation of Agricultural Grain Unloading-on-the-go. Issue 24 (2022) - Liu, Ziping; Dhamankar, Shveta; Evans, John T.; Allen, Cody M.; Jiang, Chufan; Shaver, Gregory M.; Etienne, Aaron; Vyn, Tony J.; Puryk, Corwin M.; McDonald, Brandon M.
Abstract: This paper describes the development and experimental validation of a novel grain unloading-on-the-go automation system (automatic offloading) for agricultural combine harvesters. Unloading-on-the-go is desirable during harvest, but it requires highly-skilled and exhausting labor because the combine operator must fulfill multiple tasks simultaneously. The automatic offloading system can unburden the combine operator by automatically monitoring the grain cart fill status, determining the appropriate auger location, and controlling the relative vehicle position and auger on/of. An automation architecture is proposed and experimentally demonstrated to automate the unloading-on-the-go process. To allow for diferent operator-selected unloading scenarios, the automatic offloading controller has three fill strategies and two movement control options, "open-loop" and "closed-loop". The automatic offloading controller was implemented on a dSPACE MicroAutoBox II and integrated into a combine harvester. In addition, a stereo-camera-based perception system was connected to the automatic offloading controller via an Ethernet cable for grain fill profile measurement during unloading. In-feld testing demonstrated that the automatic offloading system can effectively automate the unloading-on-the-go of a combine harvester to fill a grain cart to the desired level under nominal harvesting conditions.